Case report: Toripalimab plus anlotinib in postoperative recurrent renal pelvic sarcomatoid urothelial carcinoma - Hu, Xinrong; Deng, Lin; Pan, Yufei; Zhang, Guozhen; Ruan, Xiaolan; Jiang, Xinlan; Shen, Hao; Zhao, Lei; Dong, Jun (Frontiers in Oncology, 2024)
BackgroundSarcomatoid urothelial carcinoma (SUC) is a rare renal malignancy. Its biological malignancy is high, the prognosis is poor, diagnostic and treatment options are few, and there is no standard treatment plan.Case presentationIn this case, a 64-year-old woman was hospitalized with fever and lower back pain one week previously. The preliminary diagnosis was a right kidney stone with a urinary tract infection. After the anti-infection treatment, a percutaneous right nephrostomy was performed. The intraoperative biopsy (renal pelvis) finding was infiltrating urothelial carcinoma with a sarcomatoid variation. Subsequently, radical surgery was performed for cancer of the right renal pelvis. Implant metastasis of the abdominal wall and adjacent abdominal cavity occurred half a month after the surgery. The lesion was resected again, and two cycles of doxorubicin plus carboplatin chemotherapy were administered. However, the disease progressed more rapidly after the chemotherapy. With the written consent of the patient, the treatment was altered to targeted immune therapy with toripalimab plus anlotinib. A clinical cure was achieved after nine cycles of treatment with no obvious lesions on imaging. The maintenance therapy was administered consecutively for over a year, and the patient is at present still in good condition with a disease-free survival exceeding two years.ConclusionThis case proves that the combination of toripalimab and anlotinib is effective in the treatment of recurrent renal SUC. To the best of our knowledge, this is the first reported case of a patient with advanced recurrent urothelial carcinoma of the renal pelvis sarcomatoid cured with this therapy.